2019
DOI: 10.1158/1535-7163.mct-18-0465
|View full text |Cite
|
Sign up to set email alerts
|

The Rolipram–Perillyl Alcohol Conjugate (NEO214) Is A Mediator of Cell Death through the Death Receptor Pathway

Abstract: Glioblastoma (GBM) is a highly aggressive primary brain tumor with a poor prognosis. Treatment with temozolomide, standard of care for gliomas, usually results in drug resistance and tumor recurrence. Therefore, there is a great need for drugs that target GBM. NEO214 was generated by covalently linking rolipram to perillyl alcohol (POH) via a carbamate bond to form the rolipram-perillyl alcohol conjugate. We show here that NEO214 is effective against both temozolomide-sensitive and temozolomide-resistant gliom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To confirm whether or not NEO214 stimulated CHOP and DR5 in immunocompetent brain tumor models, GL261 mouse glioma cells were implanted into the frontal cortex of syngeneic mice. Results clearly suggested that NEO214 stimulated CHOP and DR5 (34).…”
Section: Natural Products Mediated Restoration Of Trail Pathwaymentioning
confidence: 87%
See 1 more Smart Citation
“…To confirm whether or not NEO214 stimulated CHOP and DR5 in immunocompetent brain tumor models, GL261 mouse glioma cells were implanted into the frontal cortex of syngeneic mice. Results clearly suggested that NEO214 stimulated CHOP and DR5 (34).…”
Section: Natural Products Mediated Restoration Of Trail Pathwaymentioning
confidence: 87%
“…NEO214 was chemically synthesized by covalent linkage of perillyl alcohol with rolipram using a carbamate bond (34). NEO214 was tested for efficacy against intracranial athymic tumor bearing mice and intracranial immunocompetent syngeneic mice.…”
Section: Natural Products Mediated Restoration Of Trail Pathwaymentioning
confidence: 99%
“…In this study, we used CMap analysis to accurately identify compounds that have been shown to have specific effects on GBM or other tumor types by comparing the different expression genes of GMB samples from 3 clusters. These compounds include the DNA synthesis inhibitor anisomycin ( 73 ), glutamate receptor antagonist amantadine ( 74 ), norepinephrine inhibitor amitriptyline ( 75 , 76 ), solute carrier family member inhibitor bumetanide ( 77 ), PPAR receptor agonist clofibrate ( 78 ), and fenofibrate ( 79 ), selective serotonin reuptake inhibitor (SSRI) fluoxetine ( 75 , 80 ), ATPase inhibitor helveticoside ( 81 , 82 ), norepinephrine reuptake inhibitor imipramine ( 75 , 76 , 83 , 84 ), opioid receptor agonist loperamide ( 85 ), phosphodiesterase inhibitor papaverine ( 86 , 87 ) and rolipram ( 88 92 ), polar auxin transport inhibitor quercetin ( 93 , 94 ), cyclooxygenase inhibitor rofecoxib ( 95 , 96 ), calcineurin inhibitor tacrolimus ( 97 ), purinergic receptor antagonist ticlopidine ( 98 , 99 ), HDAC inhibitor vorinostat ( 100 ), Rho associated kinase inhibitor Y-27632 ( 101 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although rolipram was never approved for marketing [174], it was considered for repurposing as an anticancer agent based on its recognized beneficial activity in preclinical cancer models [175,176]. In mouse models of intracranial glioblastoma, NEO214 revealed significant therapeutic activity [177], indicating that it was indeed able to effectively cross the BBB, as was predicted from the in silico analysis. Intriguingly, as was observed with NEO212, combination therapy with the individual components, i.e., POH mixed with rolipram, was unable to mimic the much stronger anticancer effects of the conjugated NEO214 molecule [177,178].…”
Section: Poh Conjugated To Rolipram or 3-bromopyruvate Or Valproic Acidmentioning
confidence: 98%